Modulation of the inflammatory response after sclerotherapy for hydrocoele/spermatocoele. (23rd October 2018) - Jahnson, Staffan; Rosell, Johan; Aljabery, Firas
Abstract : Objective: To investigate the modulation of the inflammatory response after sclerotherapy for hydrocoele/spermatocoele. Patients and Methods: All patients with hydrocoele or spermatocoele presenting at the Department of Urology, University Hospital, Linköping, Sweden, from 2006 to 2012, were included in this prospective observational study of sclerotherapy for hydrocoele/spermatocoele using polidocanol as a sclerosing agent and adjuvant antibiotic and anti‐inflammatory medication (AAAM) for modulation of the inflammatory response. Patients were clinically evaluated within 24–48 h after a complication or adverse event possibly related to sclerotherapy. Evaluation of cure was scheduled after 3 months and re‐treatment, if necessary was carried out in the same manner as the first treatment. Groups of patients were compared using the chi‐squared test and logistic regression analysis. Results: From a total of 191 patients, AAAM was given to 126, of whom 5% had subclinical epididymitis/swelling (SES) compared to 26% of the patients without AAAM ( P < 0.001). No other complication was observed. The rate of cure for the whole group of patients was 93% after one or two treatments and significantly higher in the group with AAAM than in the group without AAAM (96% vs 88%, P = 0.03). Conclusions: Modulation of the inflammatory response after sclerotherapy resulted in a lower incidence of SES and an increased cure rate.